2014
DOI: 10.4238/2014.january.21.13
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait locus analysis for ear height in maize based on a recombinant inbred line population

Abstract: ABSTRACT. Maize (Zea mays L.) is among the crops with the greatest worldwide economic importance. Ear height is a very important trait that is considered necessary in maize and is related to morphology, lodging, and yield. To realize its genetic basis, an F 9 recombinant inbred line population and a genetic map consisting of 101 simple sequence repeat markers were used to detect the quantitative trait locus (QTL) for ear height, and the result showed that one QTL on chromosome 1 was identified with a mapping i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Plant architecture directly affects biomass in higher plants, and particularly influences grain yields in agricultural crops. The genetics of various aspects of maize ( Zea mays L.) plant architecture, a complicated agronomic trait that is mainly determined by plant height (PH), ear height (EH), and internode number (IN), have recently been extensively investigated [ 1 3 ]. These three components reflect the spatial conformation of the maize plant, which is closely correlated with biomass, lodging resistance, and tolerance of stress associated with high plant density.…”
Section: Introductionmentioning
confidence: 99%
“…Plant architecture directly affects biomass in higher plants, and particularly influences grain yields in agricultural crops. The genetics of various aspects of maize ( Zea mays L.) plant architecture, a complicated agronomic trait that is mainly determined by plant height (PH), ear height (EH), and internode number (IN), have recently been extensively investigated [ 1 3 ]. These three components reflect the spatial conformation of the maize plant, which is closely correlated with biomass, lodging resistance, and tolerance of stress associated with high plant density.…”
Section: Introductionmentioning
confidence: 99%
“…The genetic analysis of quantitative traits is difficult and complex in maize, and quantitative traits are affected by key genes and interacting networks of small-effect genes. Therefore, different studies have provided different results including quantitative trait loci (QTL) number, distribution, and genetic effects for one trait [ 6 , 7 ]. This lack of conformity may also be explained by the many differences in parental materials, segregation-population types, ecological conditions, genetic maps, analytical methods and phenotype evaluation [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in close correspondence with the earlier observation of WIETHOLTER ( 2008) who observed an average of 2.7 alleles per locus in 23 SSR loci. LI et al (2014) observed 2.45 average numbers of alleles based on 11 SSR loci. Similarly, molecular diversity analysis of 27 maize inbred lines based on 10 SSR markers resulted in 23 polymorphic alleles with an average of 2.3 alleles per locus (ABDEL-RAHMAN et al, 2016).…”
Section: Genotyping Of Mapping Populationmentioning
confidence: 97%
“…Several researchers have reported that yield contributing traits usually exhibit stable QTLs across environments (MESSMER et al, 2009;LIU et al, 2014;ZHANG et al, 2017). Till today various researchers carried out QTL analysis for various yield traits, namely those related to ear morphology (EL, ED) (MENDES-MOREIRA et al, 2015;CHEN et al, 2016;SU et al, 2017), KR/E (VELDBOOM and LEE, 1994;AUSTIN and LEE, 1996), K/R (CHEN et al, 2016;SU et al, 2017), TW (CHEN et al, 2016;PAN et al, 2017;SU et al, 2017;ZHAO et al, 2018) and GY/P (VEIGA et al, 2012;CHEN et al, 2016;SU et al, 2017;NIKOLIC et al, 2018;RIBEIRO et al, 2018).…”
Section: Introductionmentioning
confidence: 99%